The Reality of Using Cloud Computing Applications in Teaching Language Proficiencies for the Secondary Stage from the Female Teachers' Point of View - Alenzi, Abeer Mousa (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the reality of using cloud computing applications in teaching language proficiencies for the secondary stage in Riyadh and its obstacles from the female teachers’ point of view, with an indication of the effect of the variables (academic qualification, years of experience) in that. The study relied on the descriptive survey approach, and used the questionnaire tool. It applied to a random sample of (304) secondary school female teachers in Riyadh. The study reached a number of the following results: The axis of the reality of using cloud computing applications in teaching language proficiencies got an average (1,429) with a (low) degree in the dimension of lesson planning, and the average was (1,428) with a (low) degree in the dimension of lesson implementation, and it averaged (1,433) with a (low) degree in the dimension of evaluation the lesson, and the axis of obstacles of using cloud computing applications in teaching obtained an average of (1,992), meaning the obstacles represented a (large) degree, and the results also revealed that there are differences between the views of the study sample attributable to the two variables (educational qualification and years Experience), Based on the results, the study recommends the following: Providing training courses for female teachers of language proficiencies on how to activate cloud computing applications in the educational process informs them of all new developments that occur. Providing reinforcement, both material and moral, to female teachers of language proficiencies who use cloud computing applications encourages them to use and benefits from these services. Supporting the school environment with physical equipment that allows the use of cloud computing in teaching contributes to help the teacher to activate it. Reducing the teaching and administrative burdens of teachers allows them to follow the students at the time of the class.
Keywords: reality; obstacles; cloud computing; language proficiencies; Riyadh